(untitled) - Wright, John W (London, 1995)
Contents: cycles and trends, long wave theories, empirical evidence, the fourth kondratieff downswing.,The book is organized alphabetically by state or Canadian province and then by hospital name. Each entry includes a narrative section on the history, special facilities, programs, and research done at the institution. There is also information on medical specialties available, well-known physicians on the staff, the admissions policy (including care of uninsured patients), and patient satisfaction. The "At-a-Glance" statistical profiles include number of beds, occupancy rate, average patient stay and count, annual admissions, clinic and emergency room visits, number and type of personnel, room charges, address, and telephone number. Appendixes list hospitals commended by the Joint Committee on Accreditation of Healthcare Organizations, federally funded cancer centers, and the U.S News and World Report Survey of Best Hospitals, 1994. A general index and specialists index complete the work.
Keywords: Hospitals,Bệnh viện; Directories,Thư mục; United States,Hoa Kỳ